Global trends and research hotspots in the treatment of mental disorders with transcranial magnetic stimulation: a bibliometric analysis - Ma, Zong-ke; Wei, Yi-xin; Rao, Ling; Li, Bao-jin; Gao, Qiang (Frontiers in Psychiatry, 2025)
BackgroundTranscranial Magnetic Stimulation (TMS) is increasingly utilized in the treatment of mental disorders (MD). The exploration and expanding application of various new TMS mode have significantly propelled the advancement of related clinical research.MethodsWe reviewed research published in the Science Citation Index Expanded of Web of Science Core Collection database. Using Citespace 6.1, Vosviewer 1.6.20, and Scimago Graphica 1.0.38 software, we conducted a comprehensive visual analysis of TMS on MD from multiple dimensions, including influential countries/regions, institutions, authors, and high-frequency keywords and burst keywords.ResultsA total of 611 papers between 1996 and 2023 were identified. Recently, the application of TMS on MD have gained increasing recognition. The USA leads in research publications in this field, followed by Germany and China. Institutionally, the University of Toronto in Canada ranks first (n=48); Professor Zafiris J. Daskalakis from the University of California tops among individual researchers (n=24). Cluster analysis of keywords reveal four representative clusters, demonstrating shifts in research focus and direction over time. Current hotspots focus on exploring the effectiveness of different TMS modes and stimulation targets in treating severe depression, obsessive-compulsive disorder, and schizophrenia. Analysis of burst keywords indicated that the latest research are the feasibility and safety of various emerging TMS stimulation mode for treating refractory depression, obsessive-compulsive disorder, negative symptoms of schizophrenia.ConclusionsOur study provides valuable insights into the current hotspots and emerging trends of TMS in the treatment of MD, providing a direction for future research to consider.